Thermal characterization of phase difference among the LP modes in two-mode fibers based on numerical approach - Zaini, Muhammad Khairol Annuar; Lee, Yen Sian; Lim, Kok Sing; Nazal, Nurul Asha Mohd; Yang, Hang Zhou; Ahmad, Harith (Elsevier, 2020)
In this work, we present the use of stochastic parallel gradient descent (SPGD) method for determination of thermal characteristic of the phases of LP11o and LP11e modes in relative to LP01 mode in two-mode fibers. Based on the output beam of the fiber, the composition of mode intensity and the respective phase are numerically determined. The findings indicate that modal phases of LP11o and LP11e linearly vary with increasing temperature. Their thermal sensitivities of LP11o and LP11e modes in relative with LP01 mode are determined. © 2020 Elsevier GmbH